The Mobilization of Memory and Tradition: Hong Kong’s Umbrella Movement and Beijing’s 1989 Tiananmen Movement - Johan Lagerkvist; Tim Rühlig (Contemporary Chinese Political Economy and Strategic Relations: An International Journal, 2016)
The 2014 Umbrella Movement in Hong Kong has been the most important pro-democracy protest on Chinese soil since the rise and fall of the Tiananmen Movement of 1989. Moreover, the 1989 Beijing Massacre has politicized a generation of pro-democracy activists in Hong Kong that has shaped Hong Kong’s vibrant civil society. However, while this “Tiananmen generation” has been crucial for the preparation and initial stage of the Umbrella Movement, the actual occupation was dominated by a new generation that is almost exclusively concerned with local Hong Kong politics. In light of this background, this paper compares the two democracy movements. The external environment and the goals of the two movements are markedly different. However, our comparison demonstrates striking similarities between the two movements, e.g. their internal structure and framing. Moreover, what we see as the “mobilization of memory” reflects both the continued importance of civil society structures that have been shaped by the “Tiananmen veterans” as well as the on-going renegotiation of the SAR’s relationship with the Mainland. Finally, these findings entail that the Chinese party-state will need to utilize different means to pacify the Umbrella Movement than what was done to placate democracy activists after the 1 989 crackdown.